Protocolo y estado de la ciudad del Vaticano : estado de la cuestión - Somavilla Rodríguez, Enrique (Revista de Derecho de la UNED (RDUNED), 2011)
Con el título de Protocolo y Estado de la Ciudad del Vaticano, estado de la cuestión, se ha querido desarrollar el contexto de una realidad histórica que supone la existencia permanente de la Santa Sede a través de los tiempos como sujeto con personalidad jurídica internacional, mediante el cual, la Iglesia actúa y participa en el concierto de las naciones, y por otra, la personalidad internacional del Estado de la Ciudad del Vaticano; aquélla donde se trata de la soberanía espiritual y ésta de la soberanía político-temporal. En los Pactos Lateranenses de 1929, entre Italia y la Santa Sede, Tratado político, Convención financiera y Concordato, éste fue sustituido por otro en 1984, más en concreto en el artículo 2 del propio Tratado político establece: «Italia reconoce la soberanía de la Santa Sede en el campo internacional como atributo inherente a su naturaleza, de acuerdo con su tradición y con las exigencias de su misión en el mundo». De esta manera, partiendo del concepto de protocolo y sus clases, se pretende penetrar en el inmenso mundo de las tradiciones y costumbres del Estado de la Ciudad del Vaticano, teniendo en cuenta los diversos aspectos que son necesarios para su mayor comprensión: qué entendemos al hablar de la Santa Sede o Sede Apostólica y su ceremonial; qué entendemos por Estado de la Ciudad del Vaticano y su protocolo. With the title of Protocol and State of Vatican City, state of affairs, we tried to develop the context of a historical reality that is the continued existence of the Holy See through the ages as a subject of international legal personality by which the Church operates and participates in the concert of nations, and secondly, the international personality of the State of Vatican City is one where the spiritual sovereignty of sovereignty and this political storm. In the 1929 Lateran Treaty between Italy and the Holy See, Political Treatise, financial and Concordat Convention, he was replaced by another in 1984, more specifically in Article 2 of the Treaty itself political states: «Italy recognizes the sovereignty of the Holy See in the international arena as an attribute inherent in its nature, according to their tradition and the demands of his mission in the world. Thus, from the concept of protocol and its classes, is to enter the vast world of traditions and customs of the State of Vatican City, taking into account the various aspects that are necessary for better understanding: what we understand speak of the Holy See or the Apostolic See and ceremonial; what we mean by the State of Vatican City and its p With the title of Protocol and State of Vatican City, state of affairs, we tried to develop the context of a historical reality that is the continued existence of the Holy See through the ages as a subject of international legal personality by which the Church operates and participates in the concert of nations, and secondly, the international personality of the State of Vatican City is one where the spiritual sovereignty of sovereignty and this political storm. In the 1929 Lateran Treaty between Italy and the Holy See, Political Treatise, financial and Concordat Convention, he was replaced by another in 1984, more specifically in Article 2 of the Treaty itself political states: Italy recognizes the sovereignty of the Holy See in the international arena as an attribute inherent in its nature, according to their tradition and the demands of his mission in the world. Thus, from the concept of protocol and its classes, is to enter the vast world of traditions and customs of the State of Vatican City, taking into account the various aspects that are necessary for better understanding: what we understand speak of the Holy See or the Apostolic See and ceremonial; what we mean by the State of Vatican City and its protocol.